2009
DOI: 10.1111/j.1365-2672.2009.04392.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid enumeration ofEscherichia coliin marine bathing waters: potential interference of nontarget bacteria

Abstract: Aims:  To compare the Escherichia coli quantification given by the ‘Coliplage®’ assay, based on the direct measurement of the β‐d‐glucuronidase (GLUase) activity and the reference Most Probable Number (MPN) method from seawater sites and investigate the possible interference of non‐E. coli strains in the GLUase activity measurement. Methods and Results:  Comparison performed from 69 French coastal bathing sites (1401 samples) showed nonconcordance between both methods, only for 8% of samples. Non‐E. coli 4‐met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…β-D-Galactosidase (GAL) and β-D-Glucuronidase (GUS) have been used as marker enzymes in assays for E. coli [7][8][9][10][11][12][13] while Glucosidase has been used in assays for Enterococci. Of these target enzymes GUS is the most specific, being present in 94-97% of E. coli strains tested [9,14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…β-D-Galactosidase (GAL) and β-D-Glucuronidase (GUS) have been used as marker enzymes in assays for E. coli [7][8][9][10][11][12][13] while Glucosidase has been used in assays for Enterococci. Of these target enzymes GUS is the most specific, being present in 94-97% of E. coli strains tested [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…However certain species e.g, A. viridans, Bacillus spp [22] and Vibrio harveyi (particularly in the marine environment) [8] are highly GUS positive and may interfere with an assay if present at similar numbers to the target bacteria. Further interferences can occur from chemicals in the water matrix [23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown quite a good correlation between GAL activity or GLU activity and fecal indicator bacteria in water samples, but some studies have shown no or low correlation, in particular at low levels of fecal contamination [11,12,[23][24][25][26]. The present study also indicated a low correlation between GAL activity and E. coli in coastal water at levels <1000 E. coli per 100 mL, but too few samples were included to determine a potential relationship.…”
Section: Discussionmentioning
confidence: 63%